2018
DOI: 10.12691/ajcmr-6-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Knowledge and Attitude toward Over-the-Counter Drug Use

Abstract: Introduction: With the increasing range of potent medicines available for sale 'over-the-counter' (OTC) in community pharmacies and the absence of data in Lebanon related to OTC abuse, this study sought to find opinions of the public regarding OTC medicines generally and explore views around potential misuse and abuse. Method: A cross sectional study was conducted in a community-based pharmacy setting in Lebanon. A structured random interview was used to patients visiting community pharmacy seeking for OTC dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…16) Previous studies had reported that doctors or pharmacists were the most frequent sources of medications among interpersonal channels. 15,[17][18][19] In our study, friends and/or family were most often selected at a higher rate than doctors or pharmacists. Although these sources might sometimes have professional knowledge, they are often unlikely to have any formal training in providing appropriate healthcare advice, which could lead to misuse or overuse.…”
Section: Discussionmentioning
confidence: 60%
“…16) Previous studies had reported that doctors or pharmacists were the most frequent sources of medications among interpersonal channels. 15,[17][18][19] In our study, friends and/or family were most often selected at a higher rate than doctors or pharmacists. Although these sources might sometimes have professional knowledge, they are often unlikely to have any formal training in providing appropriate healthcare advice, which could lead to misuse or overuse.…”
Section: Discussionmentioning
confidence: 60%
“…In simpler words, the respondents think that self-medication, if only practiced appropriately, is safer. A negative attitude towards the safety of self-medication with OTC drugs was also observed in studies conducted in India [21], Malaysia [22], Lebanon [23], and Northern Ireland [24]. But a study conducted in the neighboring country, Ethiopia, revealed an opposite attitude where 62.6% of the interviewees believed that non-prescription drugs are safe [13].…”
Section: Discussionmentioning
confidence: 77%
“…While friends and family may have some degree of proficient knowledge, they typically lack formal healthcare training, raising concerns about the potential for medication misuse or overuse [34]. On the contrary, earlier studies have indicated that physicians or pharmacists tend to be the primary sources of medication information within interpersonal networks [34][35][36][37]. Moreover, an earlier study revealed that social media sites were the primary source of information regarding corticosteroids for most of the participants [29].…”
Section: Discussionmentioning
confidence: 99%